Teaching Reading Comprehension by Using the Cloze Strategy: The Case of One Islamic Private Junior High School - Meidiana Eka Putri (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2020)
The aim of this study was to find out whether or not there was a significant difference on students’ reading comprehension achievement between the students who were taught by using Cloze Strategy and those who were taught by using the teacher’s method at an Islamic private junior high school in Palembang. Quasi experimental design was applied in this study. The sample was chosen by using a convenience sampling technique. Eighty one of the eighth grade students of an Islamic private junior high school in Palembang were selected as the sample of the study. The reading test was used as the instrument in collecting the data which consisted of recount and narrative texts. The test was administered twice as the pretest and post test for both experimental and control groups. In this study, the independent t-test was applied to analyze the data. The result of this study revealed that, there was a significant difference on students’ reading comprehension achievement between the students who were taught by using Cloze Strategy and those who were taught by using the teacher’s method.